Developing Digital-Based Speaking Skill Literacy Assessment Using Plomp Model to Support the National Literacy Movement - Maitri Rahmadhani (Institut Agama Islam Negeri Palopo, 2023)
This research aimed to develop a digital-based speaking literacy assessment model that credible, measurable and do able by using the PLOMP model in an effort to support the National Literacy Movement. Located in SMK Al Maksum Stabat, the subject of this research was the second graders of SMK Al Maksum Stabat by applying random sampling. The instrument used were questionnaires both used for the expert validator and for the teachers. The result showed that the digital-based speaking literacy assessment model has 90.88% of validation percentage which means it has a high level of validity but need to be revised. 85.5% respondents respond positively to the developed digital-based speaking literacy assessment model including its interest and its attractiveness. It indicated that the developed digital-based speaking literacy assessment model has fulfill the aspect of feasibility and effectiveness and has been tested successfully implemented at SMK Al Maksum Stabat.